2019
DOI: 10.1002/adsc.201901009
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Three‐Component Synthesis of Tertiary Aryl Amines from Nitro Compounds, Boronic Acids, and Trialkyl Phosphites

Abstract: The synthesis of aromatic amines is of continuous interest in chemistry. An exceptionally versatile three‐component reaction that directly transforms inexpensive nitro compounds, boronic acids, and trialkyl phosphites into tertiary aromatic amines has been realized. The reaction tolerates alkyl and aryl substituents on the nitro and boronic acid moieties, as well as functionalized phosphites. No transition‐metal catalysis is required. The method is orthogonal to other classical metal‐catalyzed syntheses since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Niggemann has found that the combination of nitroarenes with organozinc reagents in the presence of stoichiometric B 2 pin 2 results in reductive conversion to N-functionalized anilines . Recent works from our group and Csákÿ have validated a stoichiometric, phosphine-mediated reductive coupling of nitroarenes and arylboronic acids. Relatedly, Suárez-Pantiga and Sanz reported that phosphine-mediated reductive coupling of nitroarenes and boronic acids is catalyzed by an oxomolybdenum compound .…”
Section: Discussionmentioning
confidence: 99%
“…Niggemann has found that the combination of nitroarenes with organozinc reagents in the presence of stoichiometric B 2 pin 2 results in reductive conversion to N-functionalized anilines . Recent works from our group and Csákÿ have validated a stoichiometric, phosphine-mediated reductive coupling of nitroarenes and arylboronic acids. Relatedly, Suárez-Pantiga and Sanz reported that phosphine-mediated reductive coupling of nitroarenes and boronic acids is catalyzed by an oxomolybdenum compound .…”
Section: Discussionmentioning
confidence: 99%
“…Anilines play fundamentally substantial roles in both academia and industry, which therefore has triggered wide method development of nitroarene reduction . While noncatalytic reduction of nitroarenes using stoichiometric reducing agents provides currently main commercial access to functionalized anilines, these methods suffer from poor selectivity and serious ecological issues . Recent progress on catalytic reduction of nitroarenes mainly depends on transition-metal (TM) catalysis via direct hydrogenation or hydrogen transfer, electrocatalysis along with water oxidation, and sustainable visible-light-induced photocatalysis (Scheme a) .…”
mentioning
confidence: 99%
“…In 2019, Csáky reported a three-component cross-coupling reaction of nitro compounds with boronic acids and trialkyl phosphites for the synthesis of tertiary aromatic amines by the one-step construction of C(sp 2 )–N and C(sp 3 )–N bonds (Scheme 21). 41 Nitroarenes, nitroalkanes, alkylboronic acids, and arylboronic acids are compatible with this reaction system for the synthesis of tertiary amines under metal-free conditions. This method complements the classical transition metal-catalyzed approaches owing to its tolerance toward halogens and the synthesis of amino ester derivatives.…”
Section: Construction Of C(sp2)–n Bondsmentioning
confidence: 96%